Laminar Graphene Oxide Membranes Towards Selective Ionic and Molecular Separations: Challenges and Progress. Issue 4 (16th August 2019) - Ali, Akbar; Aamir, Muhammad; Thebo, Khalid Hussain; Akhtar, Javeed
Abstract: Resolution of resources and environmental crises requires an efficient separation technologies, consequently, scientists and engineers are working vigorously for ideal separation materials. Laminar graphene oxide (GO) is a two‐dimensional (2D) material offers considerable interest in this field due to its single atomic layer thickness, good stability, chemical inertness, and variety of functional groups. Recently, GO have emerged as a novel membrane material for molecular and ionic separation of gases, solvent, water, and desalination applications. This tutorial review aims to discuss the various approaches used to control the stacking of GO‐based membrane with emphasis of advantages and drawbacks associated with each approach. Further, attention will also be given to describe the recent progress in GO based membranes for ionic and molecular separations. Meanwhile, challenges and opportunities will also be discussed in detail. We hope this review expected to provide a compact source of information that will be of great interest to chemists, material scientists, physicists, and engineers working or planning to work in GO based membranes for separation applications. Abstract : In present mini‐review, we have focused the discussion on the graphene membranes, especially, fabrication methodologies for GO membranes with major focus on the advantages and disadvantages associated with these methods. Moreover, we also have discussed the recent advancements in the separation of ionic and molecular species using GO‐membranes with emphasis on the issues during separation applications.